Intrinsic viscosity of aqueous solutions of carboxymethyl guar in the presence and in the absence of salt - Badiger, Manohar V.; Gupta, Nivika R.; Eckelt, John; Wolf, Bernhard A. (Macromolecular Chemistry and Physics, 2008)
Intrinsic viscosities were determined for solutions of CMG in pure water and 0.9 wt.-% aqueous NaCl. To avoid the 0/0-type extrapolation typical for Huggins plots, a new procedure was used. For CMG and pure water, this requires only two adjustable parameters: the specific hydrodynamic volume of the polymer in the limit of infinite dilution and a hydrodynamic interaction parameter. The intrinsic viscosity of CMG (no salt) at room temperature is 6 050 mL . g(-1); approximately half as large as that of Na-PSS of comparable molar mass. The ratio of the intrinsic viscosities with and without salt is approximate to 7 for CMG, as compared to >100 for Na-PSS. The reasons 1:5 5 for the different behaviors of the two types of polyelectrolytes are being discussed.
Keywords: Biopolymers; Carboxymethyl guar; intrinsic viscosity; polyelectrolyte; salt-free solutions

Synthesis and characterization of thermo-sensitive graft copolymer of carboxymethyl guar and poly(N-isopropylacrylamide) - Gupta, Nivika R.; Ghute, Pallavi P.; Badiger, Manohar V. (Carbohydrate Polymers, 2011)
Thermo-responsive graft copolymers of carboxymethyl guar [CMG] and semitelechelic poly(N-isopropylacrylamide) [PNIPAm] were synthesized by coupling reaction between them using a water-soluble coupling agent namely, 1-(3-(dimethylamino) propyl)-3-ethyl carbodiimide hydrochloride [EDC]. The incorporation of PNIPAm into CMG was confirmed by FT-IR and NMR spectroscopy. The graft copolymers, CMG-g-PNIPAm showed enhanced viscosity as compared to the unmodified CMG in the semi-dilute regime. Due to the presence of a LCST side chains [PNIPAm], the graft copolymers exhibited thermo-responsive nature with respect to temperature which was investigated using pyrene fluorescence probe studies. Although the thermo-responsive property was observed, the thermo-thickening behavior was not seen in these polymers. The graft copolymers in the semi-dilute regime (C(p) approximate to 10-20 g/L) showed viscoelastic properties and the relaxation time, tau, could be obtained from the crossover of frequency (oh) of storage modulus (G') and loss modulus (G `') in the oscillatory experiments. The activation energy `E(a)' of associations was investigated using the time temperature superpsition (TTS). These thermo-responsive polymers along with the biodegradability of CMG can have potential application as industrial thickening agent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Poly(N-isopropylacrylamide); Thermo-sensitivity and graft copolymer

Nanocomposite of silver and thermo-associating polymer by a green route: a potential soft-hard material for controlled drug release - Gupta, Nivika R.; Bhagavatula L. V. Prasad; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2014)
Major research efforts are continuously being made to look for alternative, environment friendly green chemicals for the synthesis of nanoparticles in place of conventional and hazardous reducing agents such as sodium borohydride and hydrazine. We report here on the synthesis and characterization of AgNPs using a thermo-associating polymer namely, carboxymethyl guar grafted poly(ethylene oxide-co-propylene oxide) [CMG-g-PEPO]. The polymer acts as both reducing agent as well as stabilizing/capping agent. The formation of AgNPs with polymer was confirmed by UV/Vis spectroscopy and the TEM images indicated the size of nanoparticles to be in the range of 10-20 nm. We also demonstrated the use of these nanoparticles in the controlled release of doxorubicin hydrochloride (Dox), an anticancer drug. The binding of Dox onto the polymer and AgNPs was investigated by XPS and Raman spectroscopy which indicates that a charge-transfer mechanism is operative between the Dox and polymer holding both the entities together. The first synthesis of AgNPs using non-toxic thermo-associating polymer and subsequent release of Dox with body temperature (37 degrees C) as a trigger is the highlight of the present work.

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers